Menyikapi Radikalisme Perspektif Hadits Nabi Saw - Ali Mohtarom; Muhammad Nur Hadi; Ahmad Ma'ruf (Mu'allim, 2023)
This paper explores the management of radicalism in Indonesia as an extremist and terrorist phenomenon, drawing on the hadith of Prophet Muhammad SAW. It adopts a qualitative approach and literature review as a research methodology, using the Integrative Review model. According to the Prophet's Hadith, two approaches are suggested: preventive action and repressive action. Preventive actions involve promoting attitudes of moderation, tolerance, compassion, justice, equal rights, and caution in issuing fatwas. On the other hand, repressive measures, in line with the hadith found in Sahih Bukhari and Sahih Muslim, are directed towards addressing the actions of hypocrites and khawarij to safeguard the unity of the Muslim Ummah and protect the well-being of the Muslim community..